Injectable bone cement containing carboxymethyl cellulose microparticles as a silver delivery system able to reduce implant-associated infection risk. (June 2022) - Jacquart, Sylvaine; Girod-Fullana, Sophie; Brouillet, Fabien; Pigasse, Christel; Siadous, Robin; Fatnassi, Mohamed; Grimoud, Julien; Rey, Christian; Roques, Christine; Combes, Christèle
Abstract: In the challenging quest for a solution to reduce the risk of implant-associated infections in bone substitution surgery, the use of silver ions is promising regarding its broad spectrum on planktonic, sessile as well as multiresistant bacteria. In view of controlling its delivery in situ at the desired dose, we investigated its encapsulation in carboxymethyl cellulose (CMC) microparticles by spray-drying and included the latter in the formulation of a self-setting calcium phosphate bone cement. We implemented an original step-by-step methodology starting from the in vitro study of the antibacterial properties and cytotoxicity of two silver salts of different solubility in aqueous medium and then in the cement to determine the range of silver loading able to confer anti-biofilm and non-cytotoxic properties to the biomaterial. A dose-dependent efficiency of silver was demonstrated on the main species involved in bone-implant infection ( S. aureus and S. epidermidis ). Loading silver in microspheres instead of loading it directly inside the cement permitted to avoid undesired silver-cement interactions during setting and led to a faster release of silver, i.e. to a higher dose released within the first days combining anti-biofilm activity and preserved cytocompatibility. In addition, a combined interest of the introduction of about 10% (w/w) silver-loaded CMC microspheres in the cement formulation was demonstrated leading to a fully injectable and highly porous (77%) cement, showing a compressive strength analogous to cancellous bone. This injectable silver-loaded biomimetic composite cement formulation constitutes a versatile bone substitute material with tunable drug delivery properties, able to fight against bone implant associated infection. Statement of significance: This study is based on two innovative scientific aspects regarding the literature: i) Choice of silver ions as antibacterial agent combined with their way of incorporation: Carboxymethylcellulose has never been tested into bone cement to control its drug loading and release properties. ii) Methodology to formulate an antibacterial and injectable bone cement: original and multidisciplinary step-by-step methodology to first define, through (micro)biological tests on two silver salts with different solubilities, the targeted range of silver dose to include in carboxymethylcellulose microspheres and, then optimization of silver-loaded microparticles processing to fulfill requirements (encapsulation efficiency and size). The obtained fully injectable composite controls the early delivery of active dose of silver (from 3 h and over 2 weeks) able to fight against bone implant-associated infections. Graphical abstract: Image, graphical abstract